On the influence of van der Waals coefficient on the transverse vibration of double walled carbon nanotubes - de Borbon, Fernanda Maria (2012)
The influence of van der Waals interaction coefficient on the vibrational properties of double-walled carbon nanotubes (DWCNTs) is studied. A high order continuum beam model is used, which can be applied to study the transverse vibrations of MWCNTs, including those that could have initial deformations due to defects or external actions. A numerical study was carried out and it was found that the non-coaxial intertube frequencies are strongly influenced by the coefficient used. The importance of this result can be valued considering that the concentric structure of DWCNTs is a crucial geometrical characteristic and a non-coaxial vibration would affect their electronic and optical properties.